PRODUCTION AND ISOLATION OF POLYSACCHARIDES FROM MYCELIA OF NATURAL ISOLATES OF HIGHER FUNGI: PRODUCTION AND ISOLATION OF POLYSACCHARIDES FROM MYCELIA OF NATURAL ISOLATES OF HIGHER FUNGI - Miljkovic, Miona; Davidović, Slađana; Ilić, Nevena (Journal on Processing and Energy in Agriculture, 2026)
The traditional use of higher fungi in medicine and nutrition is largely attributed to their rich content of bioactive polysaccharides. This study evaluated the ability of four fungal isolates: Ganoderma resinaceum NMKSS, Bjerkander aadusta TMF1, Fomes fomentarius TMF2and Ganoderma sp.to produce intracellular (IPS) and extracellular polysaccharides (EPS) during submerged fermentation using glucose as the carbon source. Polysaccharides were extracted from dried mycelial biomass and culture supernatants, respectively, and quantified via the phenol-sulfuric acid assay. Initial screening revealed that EPS yields ranging from 0.1 to 0.759 mg/ml and IPS yields between 0.5 and 113.3 mg/g dry biomass. Notably, B. adusta TMF1 and F. fomentarius TMF2 exhibited significantly higher polysaccharide production and were selected for further work. The influence of organic nitrogen sources on polysaccharide yield was assessed, demonstrating that peptone supplementation maximized both EPS and IPS production. F. fomentarius TMF2 achieved the highest EPS yield of 0.84 mg/mL, conversely, B. adusta TMF1 produced a maximum IPS yield of 134.12 mg/g dry biomass. Yeast extract favored biomass accumulation but was less effective in stimulating polysaccharide synthesis. These findings suggest that nitrogen source composition critically influences the balance between fungal growth and polysaccharide production. Further research is needed to optimize culture conditions and fully exploit the biotechnological potential of these isolates for food and pharmaceutical applications.